2007
DOI: 10.1109/tps.2007.903842
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Direct-Current Surface Plasma Discharge Phenomena in High-Speed Flow Actuation

Abstract: We present a self-consistent 2-D multispecies multitemperature model of dc nonequilibrium surface plasma discharge phenomena in the presence of a low-pressure imposed high-speed convective flow. For pressures of a few torr and voltages of a few kilovolts, a nonequilibrium glow discharge is generated between the electrodes. Peak charge densities in the discharge on the order of 10 14 − 10 16 m −3 , electron temperatures on the order of 1 eV, and gas temperatures on the order of 2000 K are observed. Increasing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The results provide sup port to a number of recent applications and experi mental studies [27][28][29].…”
Section: Plasma Chemistry Processessupporting
confidence: 62%
See 1 more Smart Citation
“…The results provide sup port to a number of recent applications and experi mental studies [27][28][29].…”
Section: Plasma Chemistry Processessupporting
confidence: 62%
“…Computational modeling studies of plasma in min iaturized spaces have been recently reported [8][9][10]. The first part of this paper introduces our self consis FARAHAT, RAMADAN tent model to calculate the gas and plasma character istics produced in the microthruster because of plasma interaction at a constant electric field.…”
Section: Introductionmentioning
confidence: 99%
“…The collision cross-sections used for each species are given in Table 1; the values were determined from mobility and diffusion coefficient data in the literature. [45][46][47][48][49][50][51] As discussed previously, the collision rate for the electrons was determined from a point Boltzmann solution as a function of electron temperature ν e /N = f (T e ), and is shown in Fig. 1.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…In all of these models, simplified chemistries consisting of three species (positive ions, neutrals and electrons) are used along with the local field approximation (LFA) to determine electron and ion transport properties and rate coefficients. Deconinck et al [34] studied supersonic flow effects on a surface plasma discharge in nitrogen by imposing a fixed flowfield velocity profile.…”
Section: Continuum Models Of Plasma Dischargesmentioning
confidence: 99%